Effect of the soaking time of moringa (Moringa ole?fera) seeds on the germination and growth indicators of the plant - Padilla, C?sar; Fraga, Nidia; Su?rez, Maikel (Cuban Journal of Agricultural Science, 2012)
Through an experimental design in random blocks with factorial arrangement and five replicates, the effect of soaking the seeds of this plant during 0, 24 and 48 h on the percentage of germinated seeds and on growth indicators of the plant (percentage of leaves/plant, length and thickness of the stems, root length, length of leaves and stems and volume of the air biomass) was studied in periods of 11-15, 16-21 and 22-26 d after sowing. During the first stage, the highest germination percentage (P < 0.001) was between the 11-15 d for the seeds soaked for 24 h (86 %), without differing from those soaked for 48 h. The percentage of the germinated plants was higher (P < 0.05) between 16- 21 d, and happened in the control without soaking and did not differ from the treatment with 48 h of soaking. From 20 d after sowing on, the treatments with soaked seeds did not affect significantly the number of leaves/plant (5.0-6.0), the stem length (10.7-11.2 cm.), the root length (3.4-3.9 cm.), the stem thickness (0.20-0.22 cm.), the stem weight (0.40-0.46 g), that of the leaves (0.60-0.76 g) and the air biomass volume (5.12-5.36 cm3). It is concluded that the moringa seeds should be soaked in running water for 24 h before sowing to fasten their germination on the field. Validating these results under the field conditions is recommended. Key words: moringa, seeds, soaking, germination, growth.